Adverse Influence of Cigarette Smoking on the Endothelium - Blann, Andrew D; McCollum, Charles N (Thrombosis and Haemostasis, 1993)
The effect of smoking on the blood vessel intima was examined by comparing indices of endothelial activity in serum from smokers with that from non-smokers. Serum from smokers contained higher levels of von Willebrand factor (p <0.01), the smoking markers cotinine (p <0.02) and thiocyanate (p <0.01), and was more cytotoxic to endothelial cells in vitro (p <0.02) than serum from non-smokers. The acute effects of smoking two unfiltered medium tar cigarettes was to briefly increase von Willebrand factor (p <0.001) and cytotoxicity of serum to endothelial cells in vitro (p <0.005), but lipid peroxides or thiocyanate were not increased by this short exposure to tobacco smoke. Although there were correlations between von Willebrand factor and smokers consumption of cigarettes (r = 0.28, p <0.02), number of years smoking (r = 0.41, p <0.001) and cotinine (r = 0.45, p <0.01), the tissue culture of endothelial cells with physiological levels of thiocyanate or nicotine suggested that these two smoking markers were not cytotoxic. They are therefore unlikely to be directly responsible for increased von Willebrand factor in the serum of smokers. We suggest that smoking exerts a deleterious influence on the endothelium and that the mechanism is complex.